Adopting AI in education: optimizing human resource management considering teacher perceptions - Gârdan, Iuliana Petronela; Manu, Magdalena Beatrice; Gârdan, Daniel Adrian; Negoiță, Lucian Dragoș Leonard; Paștiu, Carmen Adina; Ghiță, Ecaterina; Zaharia, Alina (Frontiers in Education, 2025)
There is an intense concern in various fields, in order to quantify in the most complete and explicit way the impact that the accelerated development of the technology that is the basis of AI has on education. A very special issue in this context is represented by the impact AI has on the teaching methods and techniques used by teachers. Still, in order to develop and refine new methods and techniques based on AI technology is necessary that perceptions and attitudes toward this technology in general and its application in education in special to become positive and people to be open to new experiences in using it. The present research explores how different variables like perception towards inclusion of Generative AI tools within teaching materials development, degree of familiarity, challenges of AI implementation in education, importance of AI within the teaching process, resilience to change can influence the perceived utility of AI in education fostering positive attitude towards it and usage intention among teachers. The results are showing that the influence exerted by the above variables can be assessed within an empirical model that can explain the intention of teachers to use effectively AI based tools at different levels of the didactic activity. Implications at the level of human resources management in education are also discussed.